Anatomical and phenological implications of the relationship between Schinus polygama (Cav.) (Cabrera) and the galling insect Calophya rubra (Blanchard). (27th February 2018) - Guedes, L. M.; Aguilera, N.; Ferreira, B. G.; Becerra, J.; Hernández, V.; Isaias, R. M. S.
Abstract: The success of galling insects could be determined by synchronisation with host plant phenology and climate conditions, ensuring suitable oviposition sites for gall induction and food resources for their survival. The anatomical, histochemical and phenological synchronisation strategies between Calophya rubra (Blanchard) (Hemiptera: Psylloidea) and its host, the evergreen plant Schinus polygama (Cav.) (Cabrera) (Anacardiaceae), in the Mediterranean climate of southern Chile was evaluated and compared to that of the congeneric C . cf. duvauae (Scott) from Brazil and closely related host plant S. engleri in a subtropical climate. Anatomical, histometric, histochemical and vegetative phenology studies of the stem and galls were conducted from June 2015 to December 2016. Based on the anatomical, histometric and histochemical analysis, the conical stem gall traits imply gains over the non‐galled stem toward the galling insect survival, but the maintenance of phellem, secretory ducts and pith indicate conservative developmental traits that cannot be manipulated by C. rubra . Our results indicate that the conditions of the Mediterranean climate zone limit C. rubra immature activity during unfavourable periods, probably determining a diapause period and a univoltine life cycle, which are peculiarities of the S. polygama– C. rubra system. The synchronisation between development and seasonality confers peculiarities to the S. polygama– C. rubra system in the Mediterranean climate zone.